2017
DOI: 10.1007/s10815-017-0952-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of various gonadotropin and biosimilar formulations for in vitro fertilization cycles: results of a worldwide Web-based survey

Abstract: Respondents representing the majority of centers do not believe a difference exists between urinary and recombinant gonadotropins with respect to efficacy and live birth rates. While many are aware of new biosimilar recombinant FSH products entering the market, over 90% desire more information on these products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Reports from clinicians within an IVF-Worldwide web-based survey indicated that while 67.3% reported awareness of biosimilar r-hFSH products, only 25.6% had experience with biosimilar products and 92% indicated they would like more information on these products [13]. One clinically relevant approach to providing more information is the examination of effectiveness and safety within real-world, routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Reports from clinicians within an IVF-Worldwide web-based survey indicated that while 67.3% reported awareness of biosimilar r-hFSH products, only 25.6% had experience with biosimilar products and 92% indicated they would like more information on these products [13]. One clinically relevant approach to providing more information is the examination of effectiveness and safety within real-world, routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…This study is still relevant today as, although urinary gonadotropins are increasingly being replaced by recombinant gonadotropins in Germany, the D∙I∙R annual report for 2019 stated that 15.3% of stimulated ART cycles included hMG alone or in combination with r-hFSH [ 55 ]. Furthermore, a worldwide study reported that 16.4% of clinicians only/mostly prescribed urinary gonadotropins [ 56 ]. At the time of the study the preferential use of GnRH agonists was common practice in Germany, which explains why the majority of women in our analysis received a GnRH agonist (77%), with a long agonist protocol most frequently used.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, the worldwide web-based survey [ 73 ], showed that most IVF Centers (67.3%) are aware of the availability of FSH biosimilars on the market, but 90% of them require more complete information on these products. This limits the clinical use of biosimilars, as a relatively low number of centres (25.6%) reported to have clinical experience with these new products.…”
Section: Discussionmentioning
confidence: 99%